Analysis of recombination occurring at SLP1 att sites. - Lee, S C (1988)
SLP1int is a conjugative Streptomyces coelicolor genetic element that can transfer to Streptomyces lividans and integrate site specifically into the genome of the new bacterial host. Recombination of SLP1 previously has been shown to occur within nearly identical 112-base-pair att sequences on the plasmid and host chromosome. We report here that both integrative recombination and intermolecular transfer of SLP1int require no more than a 48-base-pair segment of the att sequence and that SLP1 transfer occurs by a conservative rather than a replicative mechanism. The functions responsible for the excision of the element as a discrete DNA segment are induced during the conjugal transfer of SLP1.